Green Application of Phase-Transfer Catalysis in Oxidation: A Comprehensive Review - Wang, Chuan-Hui; Liu, Chen-Fu; Rao, Guo-Wu (Mini-Reviews in Organic Chemistry, 2020)
Oxidation reactions have emerged as one of the most versatile tools in organic chemistry. Various onium salts such as ammonium, phosphonium, arsonium, bismuthonium, tellurium have been used as phase transfer catalysts in many oxidation reactions. Certainly, considerable catalysts have been widely used in Phase-Transfer Catalysis (PTC). This review focuses on the application of PTC in various oxidation reaction. Furthermore, PTC also conforms to the concept of “Green Chemistry”. • Oxidation has become one of the most widely used tools in organic chemistry and phase transfer catalysts has been widely used in oxidation. • The application of phase transfer catalysts in oxidation reaction will be summarized. • Phase transfer catalysts have important application in various oxidation reaction.
Keywords: Phase-Transfer Catalysis (PTC)